Process of cracking in reinforced concrete beams (simulation and experiment) (Fracture and Structural Integrity, 2018)
The paper presents the results of experimental and theoretical investigations of the mechanisms of crack formation in reinforced concrete beams subjected to quasi-static bending. The boundary-value problem has been formulated in the framework of brittle fracture mechanics and solved using the finite-element method. Numerical simulation of the vibrations of an uncracked beam and a beam with cracks of different size serves to determine the pattern of changes in the spectrum of eigenfrequencies observed during crack evolution. A series of sequential quasi-static 4-point bend tests leading to the formation of cracks in a reinforced concrete beam were performed. At each loading step, the beam was subjected to an impulse load to induce vibrations. Two stages of cracking were detected. During the first stage the nonconservative process of deformation begins to develope, but has not visible signs. The second stage is an active cracking, which is marked by a sharp change in eingenfrequencies. The boundary of a transition from one stage to another is well registered. The vibration behavior was examined for the ordinary concrete beams and the beams strengthened with a carbon-fiber polymer. The obtained results show that the vibrodiagnostic approach is an effective tool for monitoring crack formation and assessing the quality of measures aimed at strengthening concrete structures.
Keywords: Reinforced concrete; Crack nucleation; Vibrodiagnostics; Experiment; Mathematical modeling